Construction of Z-scheme Ag/AgVO3/carbon-rich g-C3N4 heterojunction for enhanced photocatalytic degradation of sulfamethiadiazole: DFT calculation and mechanism study - Zhixin Liu; Yongdi Liu; Xianbo Sun; Ji, Haodong; Liu, Wen; Cai, Zhengqing (Chemical Engineering Journal, 2022)
A novel Z-scheme Ag/AgVO3/carbon-rich g-C3N4 heterojunction with excellent solar-light-driven photocatalytic activity was constructed via a facile hydrothermal-calcining method. The Ag/AgVO3/carbon-rich g-C3N4 composites displayed superior performance for the photocatalytic degradation of sulfamethiadiazole (SFZ) under solar irradiation. The optimal composite with a 10 wt% Ag/AgVO3 content showed the highest photocatalytic activity, its degradation rate constant (k) for SFZ degradation was ∼13 and 30 times than that of carbon-rich g-C3N4 (CCN) and Ag/AgVO3, respectively. Furthermore, •O2– was identified as the most crucial reactive species in the Z-scheme photocatalysis system. The greatly improved photocatalytic activities are derived from the built-in electric field (BIEF) of CCN and efficient Z-scheme charge transfer with Ag nanoparticles as charge transmission-bridge. The possible photocatalytic degradation mechanism and pathway over Ag/AgVO3/carbon-rich g-C3N4 were proposed based on LC-MS analysis and density functional theory (DFT) calculation, and the toxicity of intermediates was evaluated by Quantitative structure–activity relationship (QSAR) based prediction. In summary, this work provides new insight into constructing highly efficient Z-scheme photocatalyst, which is promising for implementation in surface water remediation.
Keywords: Ag/AgVO; Antibiotics; Carbon-rich g-CN; Photocatalytic; Z-scheme heterojunction